Involvement of USP24 in the DNA damage response - Zhang, Ling (Mol Cell Oncol, 2015)
Deubiquitination has emerged as an important mechanism of regulating DNA repair pathways. We recently reported that USP24 is a novel p53 deubiquitinase that stabilizes p53 upon DNA damage. USP24 is upregulated by DNA damaging agents and plays an important role in maintaining genome stability.